Automedicación y factores asociados durante la pandemia por COVID19 en estudiantes de la carrera de Odontología - Barrera Lalangui, Fernanda Pamela (2023)
Self-treatment is a serious problem in our society; it is the initiative to take medications without a medical prescription. Due to the COVID-19 pandemic, self-treatment was carried out more frequently and its prevalence even increased among the young population. In this regard, this research was carried out to determine the factors associated with self-treatment during the COVID19 pandemic in dentistry students of “Universidad Nacional de Loja”. This study was nonexperimental, quantitative, correlational, and cross-sectional. The research technique and instrument applied were the survey and questionnaire respectively. The data collected was related to sociodemographic, economic, and sociocultural factors and the characteristics of self-treatment. For the statistical analysis and testing of the hypothesis, the Chi-Square goodness-of-fit test was used with a significance level of p<0.05. As a result, 76,4% of the students are female, 56.1% are <20 years old and 98% are single. In addition, it was determined that 49.3% were self-treated. The most commonly used medications were analgesics (32.1%) and alternative medicine (21.8%); the most persistent symptoms were cold or flu (40.3%) and headache (20.1%). Regarding the sociodemographic, economic, and cultural factors, a statistical association was found with selfmedication. This, the self-treatment problem in university students was evinced